An integrated metabolome and transcriptome analysis of the Hibiscus syriacus L. petals reveal the molecular mechanisms of anthocyanin accumulation - Wang, Xiaohong; Li, Lihua; Liu, Caixian; Zhang, Minhuan; Wen, Yafeng (Frontiers in Genetics, 2022)
Hibiscus syriacus L. var. Shigyoku is a new double-flowered bluish-purple variety in China that changes color during flower development from bluish-purple to light purple. There is limited information on the anthocyanin accumulation patterns and associated transcriptome signatures in Shigyoku from D1 (bud) to open flower (D3). Here, we employed a combined transcriptome and metabolome approach to understanding the mechanism of this color change. Our results demonstrate that cyanidins, pelargonidins, delphinidins, petunidins, peonidins, and malvidins were differentially accumulated in Shigyoku petals. The anthocyanin biosynthesis started in D1, was significantly upregulated in D2 (semi-open flower), and reduced in D3. However, malvidins, pelargonidins, and peonidins could be associated with the bluish-purple coloration on D2. Their reduced accumulation in D3 imparted the light purple coloration to Shigyoku petals on D3. Significant contributions in the color change could be associated with the expression changes in anthocyanin biosynthesis genes i.e., LARs, ANSs, DFRs, UGT79B1, C3’Hs, 3ATs, and BZ1s. The UFGTs were associated with the higher accumulation of glycosylated anthocyanins in D2 and D3. Furthermore, the changes in the expressions of the MYB and bHLH transcription factors were consistent with the anthocyanin accumulation. Finally, we discussed the possible roles of Jasmonic acid, auxin, and gibberellic acid signaling in regulating the MBW complex. Taken together, we conclude that H. syriacus petal coloration is associated with anthocyanin biosynthesis genes, the MBW complex, and phytohormone signaling.